Oxygen False Positives on Habitable Zone Planets Around Sun‐Like Stars. Issue 2 (13th April 2021) - Krissansen‐Totton, Joshua; Fortney, Jonathan J.; Nimmo, Francis; Wogan, Nicholas
Abstract: Oxygen is a promising exoplanet biosignature due to the evolutionary advantage conferred by harnessing starlight for photosynthesis, and the apparent low likelihood of maintaining oxygen‐rich atmospheres without life. Hypothetical scenarios have been proposed for non‐biological oxygen accumulation on planets around late M‐dwarfs, where the extended pre‐main sequence may favor abiotic O2 accumulation. In contrast, abiotic oxygen accumulation on planets around F, G, and K‐type stars is seemingly less likely, provided they possess substantial non‐condensable gas inventories. The comparative robustness of oxygen biosignatures around larger stars has motivated plans for next‐generation telescopes capable of oxygen detection on planets around sun‐like stars. However, the general tendency of terrestrial planets to develop oxygen‐rich atmospheres across a broad range of initial conditions and evolutionary scenarios has not been explored. Here, we use a coupled thermal‐geochemical‐climate model of terrestrial planet evolution to illustrate three scenarios whereby significant abiotic oxygen can accumulate around sun‐like stars, even when significant noncondensable gas inventories are present. For Earth‐mass planets, we find abiotic oxygen can accumulate to modern levels if (1) the CO2 :H2 O ratio of the initial volatile inventory is high, (2) the initial water inventory exceeds ∼50 Earth oceans, or (3) the initial water inventory is very low (<0.3 Earth oceans). Fortunately, these three abiotic oxygen scenarios could be distinguished from biological oxygen with observations of other atmospheric constituents or characterizing the planetary surface. This highlights the need for broadly capable next‐generation telescopes that are equipped to constrain surface water inventories via time‐resolved photometry and search for temporal biosignatures or disequilibrium combination biosignatures to assess whether oxygen is biogenic. Plain Language Summary: Next‐generation telescopes will search for life on exoplanets by looking for the spectral signatures of biogenic gases. Oxygen has been considered a reliable biosignature gas, especially for planets around sun‐like stars where non‐biological, photochemical production is unlikely. This motivates plans for future telescopes specifically designed for oxygen detection. Here, we develop a coupled model of the atmosphere‐interior evolution of terrestrial planets to show that lifeless planets in the habitable zone could develop oxygen‐rich atmospheres relatively easily. These false positives for biological oxygen could be distinguished from inhabited planets using other contextual clues, but their existence implies next‐generation telescopes need to be capable of characterizing planetary environments and searching for multiple lines of evidence for life, not merely oxygen. Key Points: Terrestrial planets in the habitable zone of sun‐like stars may accumulate O2 ‐rich atmospheres without life This O2 accumulation requires initial volatile inventories that are either much larger or smaller than that of Earth, or a high C/H ratio Broadly capable next‐generation telescopes are required to discriminate biological oxygen from these false‐positive scenarios